Innovation, Industrial Structure Upgrading, and Environmental Regulation: A Literature Review on Drivers of High-Quality Economic Development in China - Feng , Guo; Sulaiman , Noorasiah; Karim , Zulkefly Abdul; Sieng , Lai Wei (Journal of Ecohumanism, 2024)
Recent literature reveals complex relationships among innovation, industrial structure upgrading (ISU), and environmental regulation in China’s high-quality economic development (HQED). This review finds that technological innovation enhances productivity through knowledge spillovers, while green innovation and digital transformation create additional benefits via sustainability and market restructuring. ISU complements these effects by optimizing resource allocation and enhancing regional resilience. Environmental regulation significantly moderates these mechanisms, showing a “U-shaped” relationship between regulation intensity and development outcomes. Regional disparities are evident, with eastern regions exhibiting stronger innovation-upgrading synergies compared to central and western regions. Key challenges include addressing temporal dynamics, regional heterogeneity, and fine-tuning environmental policies to local contexts. Future research should explore variations in institutional quality and the social implications of development transformation.